Dziecko przed lustrem, czyli w poszukiwaniu swojego miejsca - Doda-Wyszyńska, Agnieszka (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The article is the cultural studies view on a child’s developmental difficulties in the modern world. I illustrate the theories of Lacan (the mirror stage) and Vygotsky (which describes the development as a complex functional relationship between speech, tool using and field of vision) with the 2006 movie Little Miss Sunshine directed by Jonathan Dayton and Valerie Faris. The movie is an attempt to show relationships in a family where each member is faced with a different kind of crisis. I refer also to Ariès’s The history of childhood to show that „childhood” is still a cultural matter.
Keywords: lustro; Edyp; dziewczynka – kobieta; konkurs